"I thought that I had to be alive to repay my parents": Filial piety as a risk and protective factor for suicidal behavior in a qualitative study of Chinese women. (February 2022) - Lam, June Sing Hong; Links, Paul S.; Eynan, Rahel; Shera, Wes; Tsang, A. Ka Tat; Law, Samuel; Fung, Wai Lun Alan; Zhang, Xiaoqian; Liu, Pozi; Zaheer, Juveria
Filial piety involves the Confucian view that children always have a duty to be obedient and to provide care for their parents. Filial piety has been described as both a risk and a protective factor in depression and suicide. This qualitative study aimed to explore the role of filial piety in the suicidal behavior of Chinese women. Qualitative interviews were conducted with Chinese women with a history of suicidal behavior living in the Beijing area ( n = 29). Filial piety data were extracted and analyzed in accordance with constructivist grounded theory. The women described five specific family and filial piety factors and how they influenced their ability to fulfill family role obligations, which was described as a nexus connecting these factors to depression, suicidal behavior, and recovery. The five factors were: 1) rigidity of parental filial expectations, 2) perception of family relationships as positive/supportive or negative/harsh, 3) whether filial piety is of high or low personal value in the woman's life, 4) any experiences of rebellion leading to punitive consequences, and 5) how much filial piety she receives from her children. These factors could inform suicide risk assessments in this population. They can be harnessed as part of recovery and protect against future suicidal behavior.